PH-Control of Oxidative Degradation of Methylene Blue Over Octahedral Molecular Sieve Cryptomelane-Type Manganese Oxide (OMS-2) and Fe-OMS-2. (November 2019) - Sandra, I; Muhdarina,; Anggraini, R; Siregar, S S; Awaluddin, A
Abstract: The octahedral molecular sieve cryptomelane-type manganese oxide (OMS-2) and Fe-doped OMS-2 (1%, 5%, 10%) were successfully synthesized by the redox reaction between KMnO4 and citric acid using the sol-gel method. The sol products were heated at 120°C and followed by calcination at 600°C. The as-synthesized pristine manganese oxide and Fe-OMS-2 were then characterized by XRD to determine their crystallinity and phase structure. The XRD results indicated that both the pristine and Fe-doped manganese oxides produced tunnel cryptomelane-type manganese oxides. No other peaks due to other phases are detected, indicating that Fe ions are well distributed in the framework of cryptomelane. The oxidative activities, either the pristine and Fe-OMS-2, were evaluated for degradation of methylene blue (MB) at pH ranges 2-6 by the addition of HCl solution. The oxidative tests showed that the oxidative degradation of methylene blue greatly increase with a decrease in solution pH and decrease with an increase in concentration Fe species in Fe-OMS-2 compared to pristine cryptomelane.